2022
DOI: 10.1186/s12967-022-03423-6
|View full text |Cite
|
Sign up to set email alerts
|

5-fluorouracil treatment of patient-derived scaffolds from colorectal cancer reveal clinically critical information

Abstract: Background Colorectal cancer is a commonly diagnosed cancer worldwide. Unfortunately, many patients do not respond to standard chemotherapy treatments and develop disease relapse and metastases. Besides cancer cell specific genetic changes, heterogeneity in the tumor microenvironment contribute to the clinical presentation of the disease and can potentially also influence drug resistance. By using a recently developed patient-derived scaffold method monitoring how a standardized reporter cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The PDS method has earlier been shown to maintain tumor tissue heterogeniety in vitro, producing quantitative assessments of the activity of the TME when studying cancer cell lines adapted to various PDS-based cell cultures [2]. Specific gene changes in the cancer population induced by the heterogenous PDS culture conditions have also been linked to clinical observations, validating the selected strategy for this study [2][3][4][5].…”
Section: Proteomics Of Cell-free Breast Cancer Scaffolds Identify Cli...mentioning
confidence: 58%
“…The PDS method has earlier been shown to maintain tumor tissue heterogeniety in vitro, producing quantitative assessments of the activity of the TME when studying cancer cell lines adapted to various PDS-based cell cultures [2]. Specific gene changes in the cancer population induced by the heterogenous PDS culture conditions have also been linked to clinical observations, validating the selected strategy for this study [2][3][4][5].…”
Section: Proteomics Of Cell-free Breast Cancer Scaffolds Identify Cli...mentioning
confidence: 58%
“…Furthermore, when the compounds were associated, the cytotoxic effect was enhanced, with approximately 13% of the cells remaining viable. A thorough review of the literature in the field led to the selection of the concentrations of 5-FU used in this study [51][52][53]. A study conducted by Srimuangwong et al assessed the effects of 5-FU at doses between 5 and 25 µmol/L on HT-29 cells, and it was found that the concentration of 25 µmol/L resulted in a reduction in viability below 80% after 48 h [54].…”
Section: Discussionmentioning
confidence: 99%
“…The data illustrating that IL-6, IL-8 and the receptors sortilin, IL-6R and IL-6-ST were highly secreted from PDS-adapted breast cancer cell lines support the fact that the PDS model includes a microenvironment promoting the cancer stem cell population. In addition, the PDS model could provide information on patients with an IL-6-and progranulin-inducing microenvironment that could benefit from anti-sortilin therapy [27,[55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%